Implementation and Quality of Corporate Water Reporting Based on GRI 303:2018: A Scoping Review - Ratri Nur Alfianti (Sekolah Tingg Ilmu Ekonomi Y.A.I Jakarta - Indonesia, 2026)
Abstract - Global water scarcity and climate change urgently demand substantive corporate transparency in water management, yet the extent to which GRI 303:2018 has advanced this goal remains insufficiently mapped in the literature. This study aims to (1) map corporate water reporting patterns, (2) identify implementation challenges, and (3) examine how reporting quality has been operationalized in empirical studies following GRI 303:2018 adoption, using a scoping review approach Arksey & O'Malley framework and PRISMA-ScR covering 8 studies from 2019-2025. Findings reveal a consistent pattern of information asymmetry: companies aggressively disclose water withdrawal (GRI 303-3) while minimally reporting discharge and consumption in water-stressed areas (GRI 303-4/5), consistent with symbolic compliance predicted by legitimacy theory. Key challenges include definitional ambiguity around